Inertia Reduction using Interaction Control Approach for Mecanum Wheeled Vehicle on Cornering Road - Norsharimie Mat Adam; Addie Irawan (International Journal of Robotics and Control Systems, 2022)
The paper presents a dynamic control approach using impedance control to reduce inertia factors acting on a Mecanum Wheeled Vehicle (MWV) on cornering roads. Inertia in a mobile vehicle is one of the issues that affect the safety and energy efficiencies of the vehicle, especially when maneuvering on cornering and confined paths. With reference to the problem statements in the dynamics analyses, velocity-based impedance control was proposed where the derived interaction translational forces on the vehicle that consider friction and touching forces on vehicle-terrain are controlled through the velocities of the vehicle. This study emphasized shaping the axial velocities input of the MWV for both longitudinal and latitude motions to control the sensitivity of the vehicle during cornering periods. The verification was done through several simulations on the proposed velocity-based impedance control on the MWV plant. The results show that the different forces on MWV axial motion were capable of reducing inertia via velocity input during the cornering period of maneuvering by increasing the stiffness and damping ratio of the controller at about 2 and 9 for stiffness x-axis and y-axis, respectively, and 15 and 10 for damping ration of the x-axis and y-axis respectively. Moreover, with the proposed controller, inertia on MWV can be controlled on the slippery road such as asphalt roads. This scenario has influenced the overall kinetic energy of the vehicle down to about 26%, thus, able to control the overdriven occurred on cornering road.